2012
DOI: 10.1002/bdrc.21026
|View full text |Cite
|
Sign up to set email alerts
|

Using Natural Disasters to Study the Effects of Prenatal Maternal Stress on Child Health and Development

Abstract: Research on the developmental origins of health and disease highlights the plasticity of the human fetus to a host of potential teratogens. Experimental research on laboratory animals has demonstrated a variety of physical and behavioral effects among offspring exposed to prenatal maternal stress (PNMS). However, these studies cannot elucidate the relative effects of the objective stress exposure and the subjective distress in a way that would parallel the stress experience in humans. PNMS research with humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
213
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(236 citation statements)
references
References 111 publications
15
213
6
2
Order By: Relevance
“…Extended prenatal exposure to maternal cortisol early in development is associated with cognitive impairment [129]. Furthermore, children born during a natural disaster (chronic stress) have both elevated cortisol levels and greater dermatoglyphic asymmetry, supporting this hypothesis [79,80].…”
Section: Stressorsmentioning
confidence: 90%
See 3 more Smart Citations
“…Extended prenatal exposure to maternal cortisol early in development is associated with cognitive impairment [129]. Furthermore, children born during a natural disaster (chronic stress) have both elevated cortisol levels and greater dermatoglyphic asymmetry, supporting this hypothesis [79,80].…”
Section: Stressorsmentioning
confidence: 90%
“…This is a significant advantage over many other traits, such as bones and soft tissues, because it allows one to infer precisely when development has been perturbed. For example, King et al [79,80] found that mothers of children who experienced a natural disaster (an ice storm) during the critical period of gestation gave birth to children with greater dermatoglyphic asymmetry than those gestating earlier or later.…”
Section: Dermatoglyphic Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal prenatal stressful life events and offspring psychotic experiences When conceptualising and measuring maternal prenatal 'distress', the literature is broadly divided into objective (independent stressful events) and subjective (psychopathology) (141,178). Studies which have used objective assessments of prenatal stress have usually ascertained the degree of exposure of the pregnant mothers to a natural or man-made disaster.…”
Section: Prenatal Risks and Early Postnatal Mediators Of Psychopathologymentioning
confidence: 99%